Electron capture in intermediate-to-fast heavy ion collisions with neutral atoms - Ševelʹko, Vjačeslav P.; Stöhlker, Thomas; Tawara, H.; Tolstikhina, I. Yu.; Weber, G. (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2010)
Electron capture processes of heavy ions, like Geq+, Xeq+, Pbq+, and Uq+, respectively, with the charge q ≈ 10-40, occurring in collisions with gaseous targets are considered in the E=0.1-100MeV/u projectile energy range. Calculations of single-electron capture cross sections are performed using the CDW and the CAPTURE computer codes. These are compared with available experimental data and CTMC (Classical-Trajectory Monte Carlo) calculations. Although the overall agreement is found to be within a factor of two, in some cases of heavy many-electron projectiles, e.g., U28+ +N2, Ar collisions, experimental cross sections at high energies are far smaller than theoretical predictions. Moreover, for these collision systems the observed energy dependencies are quite different from each other. Possible reasons for this behavior and how the theoretical models can be improved are discussed.